Difficulties On Developing Pupils’ Argumentative Writing Skills in English (Zien Journal of Social Sciences and Humanities, 2024)
Encouraging pupils to write persuasively in English is essential to their development as critical thinkers, analysts, and speakers of well-informed ideas. As persuasive reasoning and effective communication become more and more important in today's educational environment, it is both a challenge and a need to mentor students in the subtleties of creating strong arguments. In this article the intricacies and techniques involved in instructing school children in argumentative writing are examined.